Raising And Verb Serialization In English And Arabic: A Generative Transformational Approach - Amin, Gehad M (Universitas Islam Negeri Maulana Malik Ibrahim Malang, 2024)
This article helps bridge the gap left unfilled in the analysis of serialization in classical Arabic of the pre-Islamic period and what follows it on the one hand and between English and classical Arabic on the other. This article's premise is that serialization can be hypotactic or paratactic, where the clausal structure in both types differs. Under the theoretical concept of Raising, adapted from the generative transformational model, this feature is treated in a comparative/ contrastive fashion in both English and Arabic to determine the points of convergence and divergence and how the referential and referential interpretation is conducted by applying the PRO element. Theoretical analysis is maintained by traditional examples from Qur'anic texts and other devised examples that serve the purposes of relevant analysis.